Rhetorics and realities of participation: the Ethiopian agricultural extension system and its participatory turns. Issue 4 (1st October 2020) - Leta, Gerba; Kelboro, Girma; Van Assche, Kristof; Stellmacher, Till; Hornidge, Anna-Katharina
ABSTRACT: We present a context-sensitive perspective on participation in rural development, revolving around the reconstruction of unique sets of differences between rhetorics and realities. Using a theoretical frame inspired by the Evolutionary Governance Theory, we identify mechanisms of reinterpretation and delimitation of participation in the context of evolving rural governance. Through a detailed case study of the Ethiopian agricultural extension system, we observed that various path dependencies, interdependencies, and goal dependencies in the extension system but notably also in the embedding system of rural governance limit and shape farmers' participation. It is argued that the precise difference between official state rhetoric and on-the-ground realities of participation become understandable through reconstruction of embedding governance paths, and that the difference is further defined by relating it to the way other key concepts in rural development are implemented: decentralization, self-governance, and agricultural extension itself. Mapping out these coevolving rhetorics and realities gives insights in real reform options, for extension in particular and rural governance in general. Our case findings show that despite numerous reforms in the agricultural extension system and a steady increase in the extension coverage with a huge number of extension workers (Development Agents), participatory approaches largely failed to meet farmers' needs.